Answer:
K
K -> H
H
B -> ~H
H not B (sorry I couldn't type out the symbol)
~B
Explanation:
Verbally, what's happening is this:
We have an assertion of K. Since K -> H (K implicates H), and B -> ~H (B implicates a negation of H), a negation of B (~B) is proven. (In this entire process, nothing is given about the symbols except K is true, hence the assertion, which then implicates that H is true and that B is negated since B implicates that negated H is true when in fact it is the opposite.)
Formally, the answer would be the following:
K
K -> H
H
B -> ~H
H not B (sorry I couldn't type out the symbol)
~B
Hope this helped!